"Tax" and "Fee" Frames in Green Advertisements: The Influence of Self-Transcendence in Reusable Bag Usage. (2nd November 2017) - Muralidharan, Sidharth; Sheehan, Kim
ABSTRACT: Increasing the use of reusable shopping bags is one of many actions that consumers can take to reduce waste and conserve energy. However, this goal is somewhat daunting because it requires a significant behavior change on the part of consumers. Taking their self-transcendence into consideration, the current study used an experimental method to examine which type of message frame best influenced shoppers to use reusable bags: a fee (gain) or a tax (loss). Findings show that high self-transcendent participants were more environmentally conscious and that, overall, a penalty framed as a tax was more effective. Implications are discussed.